Comparison of urine and blood as a convenient and practical sample for estimating the contamination level of live cattle with radioactive cesium. (14th June 2019) - Sato, Itaru; Sasaki, Jun; Satoh, Hiroshi; Natsuhori, Masahiro; Murata, Takahisa; Okada, Keiji
Abstract: Blood and urine were compared to clarify which is a better sample for estimating the concentration of radioactive cesium in muscles of live cattle. The most probable concentration of 137 Cs in muscles was 21.0 times that in blood, and the error of this estimation was 28%. The concentration of 137 Cs in blood was estimated accurately using urine samples. The estimation error did not increase so much (33%), even when the concentration of 137 Cs in muscles was estimated using urine samples. On the other hand, the maximum volume of blood that can be collected with one syringe is 50 ml, whereas it is easy to collect 1, 000 ml of urine. It took at least 360 min to confirm that a cow meets the legal standard by inspecting 50 ml of blood. However, with 1, 000 ml of urine, a 20 min measurement time was sufficient for this purpose. This difference in the required measurement time is critically important for practical use. In addition, urine can be collected by farmers themselves, whereas the blood collection requires a veterinarian. Therefore, urine is a more convenient and practical sample for estimating the contamination level of live cattle with radioactive cesium.